Managing Beef Cow Efficiency - Travis D. Maddock; G. Cliff Lamb (EDIS)
AN233, a 6-page illustrated fact sheet by Travis D. Maddock and G. Cliff Lamb, discusses three key points for managing beef cow efficiency — cow weight, milking potential, and body condition score. Includes references. Published by the UF Department of Animal Sciences, February 2010.